Polemic on Corruption Cases in Bengkulu Province during Ridwan Mukti's Reign - Daafi Aqshal Sonjaya; Muhammad Faridz Adrian; Andi Deandra Putra (Daengku: Journal of Humanities and Social Sciences Innovation, 2023)
The purpose of this research is to find out polemic on corruption cases in Bengkulu Province during Ridwan Mukti’s Reign. This type of research is descriptive qualitative. The data source used secondary data sources originating from books and scientific journals. The corruption case involving the Governor of Bengkulu, Ridwan Mukti, and related parties shows the continuation of corrupt practices in the government environment. In the chronology outlined, involvement in accepting bribes related to development projects, providing positions with personal interests, and threats to contractors who did not support certain politics were revealed. This case contains serious impacts not only at the individual level, but also on society, politics, economics, and bureaucracy.